2009
DOI: 10.1210/en.2008-1437
|View full text |Cite
|
Sign up to set email alerts
|

The Sodium-Iodide Symporter NIS and Pendrin in Iodide Homeostasis of the Thyroid

Abstract: Thyroid hormones are essential for normal development and metabolism. Thyroid hormone biosynthesis requires iodide uptake into the thyrocytes and efflux into the follicular lumen, where it is organified on selected tyrosyls of thyroglobulin. Uptake of iodide into the thyrocytes is mediated by an intrinsic membrane glycoprotein, the sodium-iodide symporter (NIS), which actively cotransports two sodium cations per each iodide anion. NIS-mediated transport of iodide is driven by the electrochemical sodium gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
114
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(121 citation statements)
references
References 88 publications
(126 reference statements)
2
114
0
5
Order By: Relevance
“…Na + /K -ATPase pump provides energy for this transport system [21] . Interestingly, NIS was demonstrated to be expressed in various normal non-thyroid tissues including salivary glands, lacrimal glands, breasts, stomach, intestine, lungs, and kidneys [22,23] . This finding may be associated with both the early/short-term and late/long-term side effects of RIT, including sialadenitis, xerostomia, gastritis, nausea/vomiting, dental caries, taste dysfunction, dry eye, and pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Na + /K -ATPase pump provides energy for this transport system [21] . Interestingly, NIS was demonstrated to be expressed in various normal non-thyroid tissues including salivary glands, lacrimal glands, breasts, stomach, intestine, lungs, and kidneys [22,23] . This finding may be associated with both the early/short-term and late/long-term side effects of RIT, including sialadenitis, xerostomia, gastritis, nausea/vomiting, dental caries, taste dysfunction, dry eye, and pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that D3 and NIS contribute to regulation of the maternofetal thyroid hormone metabolism. NIS expression has been shown in the thyroid gland as well as in other tissues such as the salivary gland and milkproducing breast tissue [3][4][5]. NIS expression has also been shown in placenta, but at lower levels than those in the thyroid [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…NIS expression has also been shown in placenta, but at lower levels than those in the thyroid [6,7]. Thyroid-stimulating hormone (TSH) and iodide are two main regulators of NIS expression in the thyroid gland [5,8]. The mechanism of placental NIS expression is not yet clear, but iodide and human chorionic gonadotropin have been claimed to have a role [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that I -uptake depends on the Na + /I -symporter (NIS), whereas the uptake of I 2 is probably mediated by facilitated diffusion (6)(7)(8). I 2 supplementation exerts antitumor effects in thyroid, breast, neuroblastoma and lung carcinoma by arresting the cell cycle (increases p53 and p21 proteins), inducing apoptosis (dissipates mitochondrial membrane potential and increases Bax, caspases 3 and 7) and reducing mRNA expression of invasion genes (vascular endothelial growth factor [VEGF] and urokinase-type plasminogen activator [uPA]) (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The pathways by which I 2 inhibits the carcinogenic process are not fully understood, but contributions of both direct (anti-or prooxidant) and indirect mechanisms (generation of iodolipids, iodinated derivatives of arachidonic acid) have been proposed (5). 6-Iodolactone (6-IL) is an iodolipid that reproduces some of the antitumorogenic effects mentioned above, and it has been suggested that 6 by immunohistochemistry), p53 and p21 expression (by qPCR) and apoptosis (relative amount of nucleosomes by enzyme-linked immunosorbent assay) were evaluated. In both age-groups, normal and tumoral prostates take up both forms of iodine, but only I -uptake was blocked by perchlorate.…”
Section: Introductionmentioning
confidence: 99%